The Influence of Capital Expenditure, Leverage, and Dividend Policy on the Relative Value of Non-Financial Companies Listed on the IDX - Vicky Vicky; Dewa Gede Wirama (International Journal of Economics, Management and Accounting, 2024)
The research aims to analyze the impact of capital expenditure, leverage, and dividend policy on the relative value of non-financial companies listed on the Indonesia Stock Exchange. Using a quantitative method and multiple linear regression analysis, data were collected from the financial statements of companies over a certain period. Descriptive statistical tests, classical assumption tests, and hypothesis tests were conducted to analyze the data. The results indicate that capital expenditure and leverage do not have a significant impact on the relative value of the companies, while dividend policy has a positive and significant effect. These findings have important implications for investors in considering a company's dividend policy before making investments. For companies, the results serve as a reference to pay more attention to dividend policies in efforts to increase the relative value of the company.